When is Foreign Aid Effective in Fighting Terrorism? Threshold Evidence - Simplice A. Asongu; John Ssozi (African Governance and Development Institute (AGDI), 2015)
Building on previous literature, we assess when foreign aid is effective in fighting terrorism using quantile regressions on a panel of 78 developing countries for the period 1984-2008. Bilteral, multilateral and total aid indicators are used whereas terrorism includes: domestic, transnational, unclear and total terrorism dynamics. We consistently establish that foreign aid (bilateral, multilateral and total) is effective at fighting terrorism exclusively in countries where existing levels of transnational terrorism are highest. This finding is consistent with our theoretical underpinnings because donors have been documented to allocate more aid towards fighting transnational terrorist activities in recipient countries because they are more likely to target their interests. Moreover, the propensity of donor interest at stake is likely to increase with initial levels of transnational terrorism, such that the effect of foreign aid is most significant in recipient countries with the highest levels of transnational terrorism. Policy implications and future research directions are discussed.
Keywords: C52; D74; F42; K42; O38; 330; Foreign aid; Terrorism; Quantile regression